Gut Microbiota Dynamics during Chemotherapy in Epithelial Ovarian Cancer Patients Are Related to Therapeutic Outcome - Federica D’Amico (Cancers, 2021)
Epithelial ovarian cancer (EOC) is one of the most lethal and silent gynecological tumors. Despite appropriate surgery and chemotherapy, relapse occurs in over half of patients with a poor prognosis. Recently, the gut microbiota (GM) was hypothesized to influence the efficacy of anticancer therapies, but no data are available in EOC. Here, by 16S rRNA gene sequencing and inferred metagenomics, we profiled the GM of EOC patients at diagnosis and reconstructed its trajectory along the course of neoadjuvant or adjuvant chemotherapy up to follow-up. Compared to healthy subjects, the GM of EOC patients appeared unbalanced and severely affected by chemotherapy. Strikingly, discriminating patterns were identified in relation to the therapeutic response. Platinum-resistant patients showed a marked temporal reduction in GM diversity and increased instability with loss of health-associated taxa and increased proportions of Coriobacteriaceae and Bifidobacterium. Notably, most of these microorganisms are lactate producers, suggesting increased lactate production as supported by inferred metagenomics. In contrast, the GM of platinum-sensitive patients appeared overall more diverse and stable and enriched in lactate utilizers from the Veillonellaceae family. In conclusion, we identified potential GM signatures of therapeutic outcome in EOC patients, which could open up new opportunities for cancer prognosis and treatment.